'Asymptomatic' South Auckland preschool children have significant hearing loss and middle ear disease. (November 2018) - Dickinson, Louise J.; Nimmo, Moea; Morton, Randall P.; Purdy, Suzanne C.
Abstract: Background: Seven hundred children were recalled for hearing screening at age 2–3 years due to a problem with their newborn hearing screen. They had all been well babies with no identified risk factors for hearing loss and hence were not scheduled for targeted follow-up to retest hearing. Methods: There were 485 children (69%) that attended the recall. The average age was 36 months (SD 3.7). Family ethnicity was Pacific Island (36%), Asian (26%), NZ European (13%), and Māori (11%), and there was a high level of deprivation in the study population. Children were screened using distortion product otoacoustic emission (DPOAE) and a parent or caregiver completed a 14-item questionnaire about ear health. The children that did not pass screening were given appointments for audiology testing. Children with hearing loss and/or middle ear problems were referred for otolaryngology review and further hearing assessments. Results: About one third (36%; n = 176) of children did not pass DPOAE screening; 82 (17%) had abnormal type B tympanograms and hearing loss; 29 underwent insertion of ventilation tubes, and one had a perforated tympanic membrane. There was a significant association between failed tympanometry and hearing loss (Chi-squared = 16.67, p < .001). Five children had permanent sensorineural hearing loss (SNHL), two of whom required cochlear implants for idiopathic hearing loss, with no specific risk factors. Overall 380 of 485 children screened were deemed to have normal hearing (i.e. 22% failed hearing). From the questionnaire, 15% of the caregivers with no suspicion of hearing problems did have children with significant hearing loss. Regression analysis showed that Pacific/Māori ethnicity was significantly associated with risk of hearing loss, together with questionnaire items identifying hearing problems and breathing problems. Conclusions: There is a high proportion of children in South Auckland with unsuspected hearing loss; a different approach to hearing screening is warranted for this population with high rates of middle ear disease at age 3.